Evaluation of the effectiveness and safety of oral vancomycin versus placebo in the prevention of recurrence of Clostridioides difficile infection in patients under systemic antibiotic therapy: a phase III, randomised, double-blind clinical trial - San-Juan, Rafael; Origuen, Julia; Campion, Karen; Fernández-Ruiz, Mario; Diaz-Pollan, Beatriz; Callejas-Diaz, Alejandro; Candela, Giancarlo; Orellana, Maria Angeles; Lora, David; Llorente Muñoz, Irene; Garcia, Maria Teresa; Martinez-Uña, Maite; et al. (BMJ open, 2023)
infection (CDI) is the most prevalent cause of nosocomial bacterial diarrhoea and it is strongly associated with antibiotic use. The recurrence of CDI is a growing medical problem. Data from real-life studies and one open label randomised clinical trial (RCT) suggest that secondary prophylaxis with oral vancomycin (SPV) during subsequent courses of systemic antibiotics is a promising approach for reducing the risk of CDI recurrence. Our aim is to confirm the role of SPV through a double-blind RCT. We will perform a phase III, multicentre, placebo-controlled RCT (PREVAN trial) in a 2:1 ratio in favour of SPV (experimental treatment), in four tertiary care hospitals in Spain. Adult patients (≥18 years) with a previous history of CDI in the previous 180 days and with requirement for hospitalisation and systemic antibiotic therapy will be randomly allocated to receive either 125 mg of oral vancomycin or placebo every 6 hours for 10 days. Patients will be followed for 60 days after the end of treatment to verify a reduction in the rate of CDI recurrence in the experimental group. We assume a recurrence rate of 5% in the experimental group versus 25% in the placebo group. Accepting an alpha risk of 0.05 and a beta risk of 0.2 in a two-sided test, 104 subjects will be required in total (68 assigned to the SPV group and 34 to the placebo group). Ethical approval has been obtained from the Ethic Committee for Research with medicinal products of the University Hospital '12 de Octubre' (AC069/18) and from the Spanish Medicines and Healthcare Product Regulatory Agency (AEMPS, AC069/18), which is valid for all participating centres under existing Spanish legislation. The results will be presented at international meetings and will be made available to patients and funders. NCT05320068.